Association Analysis and Identification of Candidate Genes for Sorghum Coleoptile Color - Kai Wang; Lihua Wang; Qi Shen; Lu Hu; Zhichao Xing; Yihong Wang; Jieqin Li (Agronomy)
Coleoptile is a sheath-like structure unique to monocots and is easily observed in sorghum. Colored coleoptiles have been shown to protect plants against abiotic and biotic stresses. The purpose of this study was to identify factors controlling coleoptile color in sorghum. We phenotyped the sorghum mini core accessions for coleoptile color in two environments, determined the anthocyanin content of each color of selected accessions, carried out a genome-wide association analysis and identified a candidate gene. The phenotypic analysis showed that 95 (40% of 235) accessions were green, 28 (12%) were purple and 42 (18%) were red in both 2022 and 2023. About 12% of the accessions changed from green to red due to environmental conditions. The anthocyanin content analysis showed a positive correlation between intensity of coleoptile color and anthocyanin levels. A genome-wide association analysis identified two candidate genes, Sobic.006G175700 and Sobic.006G175500, mapped to this trait in a single locus on chromosome 6. An orthologous comparison, together with mapping, sequence analysis and qPCR, identified Sobic.006G175700 as Rs1, the gene determining the sorghum coleoptile color. The haplotype analysis with SNPs from both coding and upstream regions of Sobic.006G175700 indicates that the predominant haplotypes can differentiate between green and colored coleoptile colors. This information can be used for marker-assisted selection of desired coleoptile colors in sorghum.